The Relationship between Workload and Working Period with Nurse Response Time in Patient Handling at the Emergency Room of RSUD Dr. Abdul Rivai - M.Bahriadi; Andi Lis Garming; Rivan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2023)
Response time is an indicator of service success which is the main key to quality service in the emergency department. This study aims to determine the relationship between workload and length of service with the response time of nurses in handling patients in the Emergency Room of RSUD dr. Abdul Rivai. Using a correlational quantitative research type with a cross sectional design on 25 nurses with Spearman Rho test data analysis with a significance level of 0.05. Nurse at the IGD RSUD dr. Abdul Rivai Tanjung Redeb has an average workload of 23.20 (below normal), 6.92 years of service (moderate), and a response time of 212 seconds (3.53 minutes; responsive). There is a significant relationship between workload (Sig = 0, the nurse's response time is an indicator of service success with a benchmark for the speed of first aid which is the main key to quality service in the emergency service unit. Nurses' demands to provide services as quickly as possible with accuracy are the main obligations along with the level of patient emergency (Mahyawati & Widaryati, 2015).001; Correlation = 0.628) and length of service (Sig = 0.035; Correlation = 0.424) with nurse response time.